SISTEM INFORMASI PEMASARAN PRODUK KOPI ARABIKA GUNUNGMALANG BERBASIS ANDROID - Manurung, Ria (Catholic University Musi Charitas, 2021)
KSM Galuh Lestari is a group of coffee farmers in Gunung Malang village, Karangreja sub-district that has main activities of processing coffee into a product and marketing the product. As the location of the village is in a mountainous area with an altitude of 1400-1700 meters above sea level, the suitable coffee plant to thrive is the Arabica coffee variety. The products produced by KSM Galuh Lestari have various variants, namely green beans, roast beans, and coffee beans which are already in the form of coffee powder. Meanwhile, in terms of processing Arabica coffee beans, KSM Galuh Lestari has several types of processes, namely Natural, Full Wash Process, Honey, and Wine. KSM Galuh Lestari sold the product samples to cafes and distributors around Purbalingga Regency, marketed them individually, or displayed them in the basecamp. However, it was eventually considered less effective and efficient. The delivery cost was generally higher than the received feedback. This condition influenced both the customer and the administration system. It caused the system improperly managed. The purpose of this research is to build an information system that facilitates KSM Galuh Lestari to distribute Gunung Malang’s coffee products to all customers easily and ease the load of KSM in recording administration by using the SDLC Prototype method. The researchers used Android for this system because it is a popular platform in the community and it doesn’t take hard work to use it.